2015
DOI: 10.18632/oncotarget.6231
|View full text |Cite
|
Sign up to set email alerts
|

Tumors with high-density tumor infiltrating lymphocytes constitute a favorable entity in breast cancer: a pooled analysis of four prospective adjuvant trials

Abstract: BackgroundTumor infiltrating lymphocytes (TILs) are considered in the prognosis of breast cancer (BC) patients. Here, we investigated the prognostic/predictive effect of TILs in patients treated in the frame of four prospective trials with adjuvant anthracycline-based chemotherapy in the pre- and post-trastuzumab era.MethodsTILs density was histologically assessed as percentage of stromal area on whole routine sections of 2613 BC (1563 Luminal A/B; 477 Luminal HER2; 246 HER2-enriched; 327 triple negative [TNBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 29 publications
1
49
0
2
Order By: Relevance
“…Although in a small cohort of oral cavity carcinoma patients, the number of CD4 or CD8 T-cells was not associated with overall survival [10], a recent larger retrospective study with 278 patients showed that increased CD4 and CD8 TIL levels were significant independent prognostic variables associated with favorable overall survival and recurrence-free survival [11]. A comprehensive meta-analysis of the prognostic value of the number of TILs for HNSCC patients has not been published; but meta-analyses for patients with lung cancer and breast cancer showed that high TIL numbers were independently associated with a favorable outcome in both cancer types [12, 13]. Notably, HPV-driven HNSCC has a distinct clinical response profile to chemoradiation therapy.…”
Section: Does the Number Of T-cells In The Tumor Microenvironment Matmentioning
confidence: 99%
“…Although in a small cohort of oral cavity carcinoma patients, the number of CD4 or CD8 T-cells was not associated with overall survival [10], a recent larger retrospective study with 278 patients showed that increased CD4 and CD8 TIL levels were significant independent prognostic variables associated with favorable overall survival and recurrence-free survival [11]. A comprehensive meta-analysis of the prognostic value of the number of TILs for HNSCC patients has not been published; but meta-analyses for patients with lung cancer and breast cancer showed that high TIL numbers were independently associated with a favorable outcome in both cancer types [12, 13]. Notably, HPV-driven HNSCC has a distinct clinical response profile to chemoradiation therapy.…”
Section: Does the Number Of T-cells In The Tumor Microenvironment Matmentioning
confidence: 99%
“…TILs are more frequent in the aggressive subtypes of breast cancer. In a pooled analysis of 4 prospective adjuvant trials [18], high levels of TILs were significantly more frequent in hormone receptor-negative tumors. In the adjuvant BIG 02-98 trial, the median percentage of TILs was the highest in estrogen receptor (ER)-negative and HER2-negative tumors [19].…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 99%
“…Multiple reasons may integrate for this apparently contrasting finding. For example, the double-negatives and double-positives were highly represented among tumors with high TILs that are favorable prognosticators in TNBC (61,62), double negatives may represent genomically stable TNBC that carry a better prognosis (63), while our finding on the eitherpositive phenotype may be related to the observed worse outcome observed in patients with tumors that are p53 protein positive but do not express CK5/6 and the androgen receptor (64). Plausibly, beyond these speculations, the obtained EGFR/p53 IHC profiles should be addressed as surrogate markers integrating different genomic/molecular alterations in TNBC that need further evaluation for their prognostic value in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%